Influence of a constancy of linear contact of a sliding tribosystem on it tribocharacteristics - Костюнік, Р.Є. (Proceedings of National Aviation University (archive), 2004)
In article it is experimentally proved, that the constancy of linear contact of sliding tribosystem considerably influences its basic operational characteristics, namely antiwear and antifriction.